Colombian Orchidaceae : a catalogue of the Pleurothallidinae - Karremans Lok, Adam Philip; Moreno Silva, Juan Sebastián; Gil Amaya, Karen; Gutiérrez Morales, Nicolás; Espinosa Moreno, Felipe (2023)
Colombia is a major biodiversity hotspot, having one of the richest orchid floras in the world. The country spans over a million square kilometers of land, hosting a multitude of different ecosystems thanks to the complexity of its mountainous systems and influences from neighboring countries in Central and South America, as well as the Atlantic and Pacific coastlines. Prior studies found an estimated 3591-4270 species of orchids occurring in Colombia, making it the most species-rich plant family in the country. About 35% of those orchids are members of the Pleurothallidinae subtribe, the largest group in the family and also that with the highest rate of species discovery. Here we record 1862 species of pleurothallids for the country, a significant increase from the 1286-1529 range estimated just a few years ago. We expect Pleurothallidinae to represent close to half the Colombian orchid flora. Colombia hosts roughly one-third of all currently known taxa in the subtribe, and close to 60% of these species are found nowhere else in the world. These are clear indicators that the country is a highly important center of pleurothallid diversity and a key target for their conservation. The most species rich genera in the country are Stelis (521 species), Lepanthes (377 species), Pleurothallis (248 species) and Masdevallia (171 species). Country-level distribution is given for each accepted species. The closest floristic affinity is found with Ecuador, with which Colombia shares over 76% of the non-endemic Pleurothallidinae species, followed in the distance by Venezuela and Peru, with just above one-quarter of the non-endemics being shared. Numerous new country records are presented in the catalogue, many of which are illustrated with color photographs. We provide a full list of homotypic synonyms for each accepted taxon, as well as an annotated list of excluded taxa and newly proposed synonyms. Heterotypic synonyms are not listed, unless they are based...
Colombia es uno de los mayores centros de biodiversidad, y cuenta con una de las floras de orquídeas más ricas del mundo. Ocupa más de un millón de kilómetros cuadrados de territorio, albergando una gran diversidad de ecosistemas gracias a sus complejos sistemas montañosos, la cercanía a varios países vecinos de Centro y Sudamérica, y la influencia de las costas sobre el Atlántico y el Pacífico. Estudios previos estimaron que Colombia cuenta con alrededor de 3591-4270 especies de orquídeas, siendo la familia de plantas de mayor diversidad en el país. Alrededor de un 35% de las orquídeas reportadas de Colombia son miembros de la subtribu Pleurothallidinae, el grupo más diverso de la familia y aquel con la mayor tasa de novedades descritas. Aquí registramos 1862 especies de esta subtribu en el país, un incremento significativo del rango de 1286-1529 especies estimado solo unos pocos años atrás. Esperamos que las especies de Pleurothallidinae representen cerca de la mitad de la flora de orquídeas Colombiana. Colombia alberga cerca de una tercera parte de todas las especies que se conocen en la subtribu, y casi el 60% de estas no ocurren en ningún otro lugar del mundo. Estos son indicadores claros que Colombia es un importante centro de diversidad de estas plantas y un sitio clave para su conservación. Los géneros más diversos en el país son Stelis (521 especies), Lepanthes (377 especies), Pleurothallis (248 especies) y Masdevallia (171 especies). Para cada especie aceptada se indica la distribución a nivel de país. La afinidad florística más estrecha se encuentra con Ecuador, con quien Colombia comparte más del 76% de las especies no endémicas de Pleurothallidinae. Le siguen a distancia Venezuela y Perú, con los que se comparten poco más de un cuarto de las especies no endémicas. En el catálogo presentamos numerosos nuevos registros para el país, muchos de ellos ilustrados con fotografías. Se proporciona una lista...
Keywords: PLEUROTHALLIDINAE -- COLOMBIA; ORQUIDEAS -- COLOMBIA; BOTANICA -- COLOMBIA